Sea-ice communities: structure and composition in Baltic, Antarctic and Arctic seas - Meiners, Klaus (2002)
Sea ice is an important structural component of polar marine ecosystems but also at lower latitude seas like e.g. the northern Baltic Sea. This study summarises observations on biological, chemical and physical characteristics of sea ice and under-ice water obtained during three expeditions to the Baltic Sea, the Fram Strait area (Arctic) and the Bellingshausen Sea (Antarctica). The study aimed at a better understanding and quantification of different components of the sea ice related food web. The seasonal Baltic sea ice is least studied and therefore the work in this area focused on an inventory determination of the abundance and biomass composition of the sympagic (=ice-associated) community of the Bothnian Bay and Bothnian Sea as well as on the importance of abiotic and biotic factors in the control of ice algal accumulation. The work on the better explored polar sea ice focused on the abundance, distribution and characteristics of transparent exopolymer particles (TEP) in Arctic and Antarctic sea ice. TEP are a recently described class of exopolymeric particles, which are formed abiotically and biotically from polysaccharid-rich precursors. High amounts of TEP-precursors are released by bacteria and algae especially in response to environmental stress. In the pelagic realm TEP are important in the aggregation of diatom blooms, provide the matrix of macroaggregates and serve as substrate and habitat for attached bacteria. High concentrations of TEP have been recently described for Arctic sea ice and may have an important impact on carbon dynamics in sea-ice systems. The present study related TEP concentrations to biotic and abiotic sea ice parameters, potential modes of TEP formation were elucidated and the importance of TEP for the sea-ice habitat was discussed.